2020
DOI: 10.1155/2020/4947381
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating MicroRNAs as a Promising Diagnostic Biomarker for Cervical Intraepithelial Neoplasia and Early Cancer: A Meta-Analysis

Abstract: Background. Cervical cancer (CC) is one of the most common female malignant tumors. And cervical intraepithelial neoplasia (CIN) is the precancerous lesion of CC, which can progress to invasive CC. MicroRNAs (miRNAs) have been found to be potential diagnostic biomarkers for CIN or CC. However, recently, the lack of sufficient studies about the diagnostic value of miRNAs for CIN made it challenging to separately investigate the diagnostic efficacy of miRNAs for CIN. Likewise, the conclusions among those studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
2
15
0
2
Order By: Relevance
“…The high specificity ranges recorded from our review proved that miR-9 assay have diagnostic relevance to detect CIN2+. Although predictive values were missing in a number of studies included, sensitivity and specificity appeared to be similar across, and consistent with earlier review conducted by Jiang et al which recorded sensitivity, specificity, and AUC of 73, 94%, and 0.95, respectively, with 13.2 Positive Likelihood Ratio (PLR), and 0.28 Negative Likelihood Ratio (NLR) [53]. Experimental studies have shown that epigenetic instability is greatly influenced by miRNA which plays important role in transcriptional regulation, and any form of dysregulation as seen in overexpression often lead to a wide range of human malignancy including cervical cancer [2,3,11].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The high specificity ranges recorded from our review proved that miR-9 assay have diagnostic relevance to detect CIN2+. Although predictive values were missing in a number of studies included, sensitivity and specificity appeared to be similar across, and consistent with earlier review conducted by Jiang et al which recorded sensitivity, specificity, and AUC of 73, 94%, and 0.95, respectively, with 13.2 Positive Likelihood Ratio (PLR), and 0.28 Negative Likelihood Ratio (NLR) [53]. Experimental studies have shown that epigenetic instability is greatly influenced by miRNA which plays important role in transcriptional regulation, and any form of dysregulation as seen in overexpression often lead to a wide range of human malignancy including cervical cancer [2,3,11].…”
Section: Discussionsupporting
confidence: 82%
“…Like many other circulating miRNAs, studies have established that miR-9 could be useful for early detection of cervical cancer, predicting cancer prognosis, and in monitoring clinical outcome of cancer disease [55]. And that, by examining the associations between miR-9 levels in exfoliated cells, cervical tissues or serum; and the diverse biological processes such as metabolism and apoptosis, there is a consensus across studies showing that elevated levels is valuable for evaluating risk of cervical Intraepithelial neoplasia (CIN) in suspected individuals [2,7,53,55,57,58], especially in conjunction with other equally useful markers such as miR-21, miR-155, miR-192, miR-203 and miR-205 to improve specificity for optimal treatment benefit [2,11,48,53,[59][60][61]. Although our review is in agreement with this general consensus on diagnostic relevance of miR-9 in detection of CIN2+ [2,11], coupled with reduced turnaround time (TAT), and non-invasive blood sampling [53,55]; more robust clinical translation studies with larger consecutive cohorts of women participants would be appropriate for adequate validation alongside cost evaluation prior to implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is difficult to find more than 4 of 187 studies reporting diagnostic accuracy for a particular miRNA (miR-20a and 205) or more than 2 reporting, albeit consistent, survival hazard ratios (miR-145, -34a, -205). Interestingly, a meta-analysis has indicated that circulating miR-205 was a good diagnostic biomarker [211].…”
Section: Mirna In Hpv-associated Cancermentioning
confidence: 99%
“…and tumor suppressor miRNAs is proposed as a candidate biomarker in many cancers [9.10]. Apart from their detection in tumor tissues, several studies have also delineated the role of miRNAs derived from liquid biopsy samples, including plasma and serum, in cervical cancer [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%